Characteristics of the Chinese Gaming and Esports Market. Applications for Polish Game Manufacturers - Maciej, Walkowski; Weronika, Kempińska (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2020)
Worldwide, information and communication technologies (ICT) are creating a new post-industrial revolution, the pace, scope and importance of which are unprecedented, without being reflected in the past. Its best manifestation is the Type 4.0 Industrial Revolution. having a huge impact today not only on the living and working conditions of billions of people, but also on the directions of specialization of production and the profits accompanying them. These changes can be described as a revolution based on information, an expression of increasing human knowledge and its application. One of the more interesting manifestations of it, relatively poorly known in Poland, is the increasingly profitable and increasingly important global gaming market and the accompanying e-sports market. The dynamic development of the computer games market in the People’s Republic of China and the development of the e-sport discipline actively supported by the state authorities of this country fit perfectly into the perceived development paradigm. This research problem requires closer analysis also from a Polish perspective, motivated not only by cognitive desire, but above all by the utilitarian dimension. For the increasingly competitive polish video game manufacturers with CD Projekt SA at the forefront, the Chinese market is a great opportunity to increase profits, an opportunity – so far – still too underuly used. On the way to increasing them, in addition to real challenges, chances and opportunities, there are several fundamental barriers and risks, undoubtedly worthy of the scientific diagnosis contained in the presented article.

Na całym świecie technologie informacyjno-telekomunikacyjne (ICT) wywołują nową rewolucję postindustrialną, której tempo, zasięg i znaczenie są bezprecedensowe, nie mając odzwierciedlenia w przeszłości. Jej najlepszym przejawem jest rewolucja przemysłowa typu 4.0. mająca już dziś ogromny wpływ nie tylko na warunki życia i pracy miliardów ludzi, ale też na kierunki specjalizacji produkcji oraz zyski im towarzyszące. Zmiany owe można określić mianem rewolucji opartej na informacji będącej wyrazem rosnącej wiedzy ludzkiej i jej zastosowania. Jednym z bardziej interesujących jej przejawów, relatywnie słabo znanych w Polsce, jest coraz bardziej dochodowy i nabierający na znaczeniu globalny rynek gamingowy i towarzyszący mu rynek e-sportowy. W tak postrzegany paradygmat rozwoju świetnie wpisuje się dynamiczny rozwój rynku gier komputerowych w Chińskiej Republice Ludowej oraz aktywnie wspierany przez władze państwowe tego kraju rozwój dyscypliny e-sportu. Ów problem badawczy wymaga bliższej analizy także z polskiej perspektywy, motywowanej nie tylko chęcią poznawczą, ale przede wszystkim wymiarem utylitarnym. Dla coraz bardziej konkurencyjnych w świecie polskich producentów gier komputerowych z CD Projekt SA na czele, rynek chiński stanowi bowiem wielką szansę na wzrost zysków, szansę – póki co – nadal zbyt słabo wykorzystywaną. Na drodze do ich zwiększenia oprócz realnych wyzwań, szans i możliwości, pojawia się kilka zasadniczych barier i zagrożeń, niewątpliwie wartych diagnozy naukowej zawartej w prezentowanym artykule.
Charakterystyka chińskiego rynku gamingowego i e-sportowego. Wnioski dla polskich producentów gier
Keywords: Internet; gaming; e-sports; China; European Union; computer games; Internet; gaming; e-sport; Chiny; Unia Europejska; gry komputerowe